2019
DOI: 10.1002/jcb.29063
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differentially expressed profiles of lncRNAs, mRNAs, and miRNAs in laryngeal squamous cell carcinoma in order to construct a ceRNA network and identify potential biomarkers

Abstract: Objective This study aimed to uncover a regulatory network comprised of long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and messenger RNAs (mRNAs) in laryngeal squamous cell carcinoma (LSCC), to explore its underlying mechanisms and development, and to identify key genetic biomarkers for the prognosis of LSCC. Methods Here, we compared mRNA, lncRNA, and miRNA expression profiles between 111 LSCC and 12 adjacent normal tissues using RNA sequencing (RNA‐Seq) data from the Cancer Genome Atlas (TCGA) database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…To our knowledge, lncRNAs, miRNAs and mRNAs could comprise the so-called ceRNA network in many studies. For instance, lncRNAs, mRNAs and miRNAs compose a ceRNA network in laryngeal squamous cell carcinoma and are identified as potential biomarkers [24]. Previous study has indicated that ATXN7L3 exerts an important influence on cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, lncRNAs, miRNAs and mRNAs could comprise the so-called ceRNA network in many studies. For instance, lncRNAs, mRNAs and miRNAs compose a ceRNA network in laryngeal squamous cell carcinoma and are identified as potential biomarkers [24]. Previous study has indicated that ATXN7L3 exerts an important influence on cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…27 Notably, the integrated ceRNA network analysis with large-scale high-throughput sequence data greatly contributes to explore underlying molecular mechanisms of various cancers, including LSCC. 12,28 In this current study, we identified 2957 DEmRNAs, 61DElncRNAs and 23 DEmiRNAs, and constructed a lncRNA-miRNA-mRNA ceRNA network by analyzing the expression profiles of LSCC and normal adjacent. Firstly, functional enrichment analysis of DEmRNAs showed that they were mainly enriched in many GO terms associated with extracellular matrix organization, and several significant KEGG pathways such as DNA replication and cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have focused in part on ceRNAs in laryngeal squamous cell carcinoma (LSCC) (Kong et al, 2019;Liu & Ye, 2019;Gao et al, 2019;Zhao et al, 2019;Sun et al, 2018;Feng et al, 2016), tongue squamous cell carcinoma (TSCC) (Sturgis & Cinciripini, 2007), and nasopharyngeal carcinoma (NPC) (Fullerton et al, 2020;Agrawal et al, 2011). These studies have identified differentially expressed RNAs by lncRNA and mRNA integrated microarrays of cancer tissue or by immunohistochemistry (Gao et al, 2019;Zhao et al, 2019;Sun et al, 2018;Feng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%